DESIGN AND SYNTHESIS OF CHIRAL AND ACHIRAL 2, 3 AND 5 SUBTYPE SELECTIVE GABA(A)REGIC LIGANDS FOR TREATMENT OF CENTRAL NERVOUS SYSTEM DISORDERS AND DIFFERENT TYPES OF CANCERS - (:unkn) unknown (My University, 2023)
ABSTRACT DESIGN AND SYNTHESIS OF CHIRAL AND ACHIRAL 2, 3 AND 5 SUBTYPE SELECTIVE GABA(A)REGIC LIGANDS FOR TREATMENT OF CENTRAL NERVOUS SYSTEM DISORDERS AND DIFFERENT TYPES OF CANCERS bySepideh Rezvanian The University of Wisconsin-Milwaukee, 2023 Under the Supervision of Professor James M. Cook Part I: Design and Synthesis of Chiral α5 Subtype Selective GABA(A)ergic Ligands for Schizophrenia, Depression and Alzheimer’s DiseaseGamma (γ)-amino butyric acid, a naturally occurring amino acid, serves as a proteinogenic amino acid and acts as the principal inhibitory neurotransmitter in the central nervous system (CNS), including the cerebrum of the mammalian brain. The benzodiazepines (BZDs) bind at the extracellular interface of the α+γ2-subunits of GABAAR, influencing various brain functions. The α1-subtypes are linked to anxiolytic sedative, ataxic, amnesic, anticonvulsant, and addictive effects, while the α2/3-subtypes contribute to anxiolytic, anticonvulsant, and antinociceptive activities. α5-containing GABAARs in the CNS play a role in cognition, learning, and memory processes. Dysfunctions in these receptors in the CNS are implicated in various CNS disorders. There is an urgent need for improved medications to treat anxiety and depression, especially considering their comorbidity. Presently, no drugs on the market for depression or schizophrenia address cognition problems, representing an unmet medical need. Leveraging the "privileged imidazodiazepine (IMZD) structure," over 150 novel α5-preferring ligands have been synthesized in Milwaukee for evaluation of pro-cognitive, anxiolytic, and antidepressant activity. The lead compounds, GL-II-73 and GL-I-54 (developed by Guanguan Li) were identified as anxiolytic, antidepressant, and pro-cognitive—a significant discovery. GL-I-54 was resynthesized and evaluated for additional biological activity. The ligand showed symptomatic, disease-modifying, and neurotrophic effects in a mouse model of chronic stress, reversing stress-induced and age-related working memory deficits in both old and young mice. DAMONA PHARMACEUTICALS is currently conducting further studies to advance GL-I-54 towards clinical applications for depression and potentially Alzheimer's disease. Additionally, some other novel α5-subtype selective ligands were synthesized based on the structure of GL-I-54 and evaluated for pro-cognitive and anxiolytic. Among these ligands, the amide analog SRE-II-11 showed pro-cognitive effects in primary and secondary screenings using the Y-maze assay. This ligand will undergo further testing in the forced-swim test and elevated plus maze to determine their anti-depressive and anxiolytic behavioral profile. Furthermore, the 1,2,4-oxadiazoles SRE-II-42 and SRE-III-07 demonstrated strong pro-cognitive profiles in the Y-maze assay, suggesting their potential as key backups for ligand GL-I-54, pending further assessments in tests such as the forced-swim test, UCMS, elevated plus maze, metabolism, etc. Part II: Design and Synthesis of Achiral α2/3 Ligands for Anxiety, Epilepsy, and Pain: Large scale Synthesis of Hz-166 and Analogs Epilepsy, a prevalent neurological condition, is a leading cause of neurological disability, affecting approximately 1-2% of the global population, with about 33% of patients experiencing refractory epilepsy. Various drugs, including the widely prescribed benzodiazepine class (e.g., Valium and Xanax), are available for treatment of neurological disorders such as epilepsy and anxiety. Unfortunately, patients often develop tolerance to benzodiazepines, and mostly they are effective for only around 3 days in status epilepticus. These drugs, known to bind non-selectively at the subtypes to the α and γ interface of the gamma-aminobutyric acid type A (GABAA) receptor, lead to adverse effects, encompassing tolerance, addiction, sedation, ataxia, somnolence, and confusion. The novel imidazodiazepine agent HZ-166 was developed in Milwaukee and it was identified as α2/α3 receptor subtype-selective ligands, demonstrating anxiolytic and anticonvulsive activities without undesirable side effects like sedation and ataxia. However, the ester function in HZ-166 (6) was prone to metabolism into the less active corresponding carboxylic acid, resulting in poor exposure, high clearance, and limited blood-brain barrier penetration. The strategic replacement of the ester with heterocycles, specifically oxazoles, significantly enhanced metabolic stability and pharmacokinetics. This improvement led to the development of the clinically advancing non-sedating anticonvulsant, KRM-II-81. As part of ongoing efforts, analogs based on the structure of KRM-II-81 were designed and synthesized. Utilizing docking procedures in the human full-length heteromeric α1β3γ2 GABAA receptor subtype CryoEM structure (6HUO), following the protocols outlined by Masiulis et al. in Nature, 2019, their biological activities were tested. Crucially, several novel analogs of oxazole and oxazoline have demonstrated potent anticonvulsant activity, showcasing improved in-vivo and in-vitro stability without inducing cytotoxicity, sedation, ataxia, or loss of righting response. Among all the novel KRM-II-81 bioisosteres designed and synthesized, ZK-III-58 featuring an 8-bromo substituted imidazodiazepine as well as ZK-IV-07 exhibited enhanced exposure at the target site (brain) and improved metabolic stability in both plasma and brain. This translated to improved oral bioavailability, aligning precisely with the requirements for pre-clinical studies. ZK-III-58 demonstrated great efficacy in various epilepsy models such as pentylenetetrazole (metrazole) induced clonic and tonic seizure models. Significantly, ZK-III-58 exhibited full potency in therapy-resistant seizure models, non-convulsive status epilepticus models, and chronic seizure models. Its anticonvulsant activity remained potent through intraperitoneal (i.p.) or oral administration in both mice and rats. Remarkably, this 1,4-oxazole displayed a favorable toxicity profile and selectively bound to the rat brain benzodiazepine receptor site without undesired binding to other receptors, including HERG. ZK-III-58 did not induce sedation, ataxia, or loss of righting response, even at doses up to 120 mg/kg, and showed non-toxicity in the HEK-293 cell line. The synthesis of ZK-III-58 was successfully executed without employing column chromatography in any synthetic step and without the need for toxic and expensive palladium. Undoubtedly, as a GABAA potentiator and potentially α2/α3 receptor subtype-selective compound, ZK-III-58 and ZK-IV-07 serve as potent and safe backup anticonvulsant agents to the clinically advancing KRM-II-81 for the treatment of epilepsy. Part III: Design and Synthesis of α5 Subtype Selective GABA(A)ergic Ligands for Treatment of Different Types of Cancer Gamma-aminobutyric acid type A receptors (GABAARs) are transmembrane pentameric ligan-gated ion channel in the central nervous system, responding to GABA as the principal inhibitory neurotransmitter. This study focuses on designing ligands for the extracellular interface of GABAAR α and γ2-subunits, aiming to selectively modulate subtypes for therapeutic benefits. Specifically, α5 plays a crucial role in CNS disorders, such as schizophrenia and major depressive disorders. Medulloblastoma, the most prevalent pediatric brain tumor, is classified into four subgroups: WNT, SHH, Group 3, and Group 4. Among these, Group 3 exhibits the highest morbidity, relapse, and metastasis rates. Conventional treatment involves surgical tumor removal, followed by radiation and chemotherapy, leading to adverse effects like hearing impairment, permanent damage to the endocrine system, neurocognitive function impairment, and secondary tumors. Due to these issues, medulloblastoma needs better treatment. Notably, Group 3 tumors display elevated expression of the α5 subunit of ligand-gated ionotropic γ-aminobutyric acid type A receptors.Positive allosteric modulators like KRM-II-008 and QH-II-066 targeting α5 GABAAR subunits exhibit promising results against Group 3 medulloblastoma. Analogs of KRM-II-008 and QH-II-066, synthesized and assayed, demonstrate potent anti-cancer effects, suggesting their potential as efficient drugs. Melanoma, a deadly skin cancer, shows high expression of α5 GABAAR subunits. QH-II-66, a benzodiazepine, proves effective in sensitizing melanoma cells to radiation and immune checkpoint inhibitors. Additionally, testing in H1792 lung cancer cell lines reveal their activity, and a novel compound, SRE-III-35, emerges with enhanced efficacy and improved synthesis. These benzodiazepine-based anticancer drugs exhibit rapid blood-brain barrier penetration, enhancing their therapeutic potential. Furthermore, their non-toxic nature for normal cells, coupled with anxiolytic effects, could offer clinical significance, especially in combination therapies. The study concludes with the potential clinical relevance of these promising anticancer agents.